Global Impact of Breach of Good Faith in Insurance Contracts: Dampak Global Pelanggaran Itikad Baik dalam Kontrak Asuransi - Nugraha, Delsa Wahyu; Setyawan , Fendi; Soetijono, Iwan Rachmad (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the principle of utmost good faith (itikad baik) in insurance contracts, which mandates full and honest disclosure by all parties to prevent agreement nullification. Despite its critical importance, the enforcement and consequences of breaches are poorly documented, particularly regarding legal outcomes and claims processes. Through normative legal research utilizing primary and secondary sources, this research examines the implications of such breaches and suggests regulatory enhancements. Key findings indicate breaches can lead to contract cancellation, claim denial, or legal actions. The study highlights the necessity of regulatory improvements and increased notarial involvement to ensure equitable and transparent insurance practices. Highlights: Critical Role of Disclosure: Utmost good faith requires complete honesty from all parties in insurance contracts. Consequences of Breach: Violations can lead to severe outcomes like contract termination and denied claims. Need for Regulation: Suggests stronger legal frameworks and notarial oversight to ensure fairness and transparency. Keywords: Utmost Good Faith, Insurance Contracts, Legal Implications, Regulatory Enhancements, Notarial Involvement